Answer:
1) When x is 1, y is 4, and vice versa
2) When x is -6, y is 42, and when x is 7, y is 114
3) When x is -2, y is 2, and when x is 8, y is 42
Step-by-step explanation:
1)
![y=x^2-6x+9](https://tex.z-dn.net/?f=y%3Dx%5E2-6x%2B9)
which can be rearranged as
.
Substituting this lone y into the first equation, you get:
![5-x=x^2-6x+9](https://tex.z-dn.net/?f=5-x%3Dx%5E2-6x%2B9)
Move everything to one side:
![x^2-5x+4=0](https://tex.z-dn.net/?f=x%5E2-5x%2B4%3D0)
Factor:
![(x-4)(x-1)=0](https://tex.z-dn.net/?f=%28x-4%29%28x-1%29%3D0)
![x=1, 4](https://tex.z-dn.net/?f=x%3D1%2C%204)
![y=4, 1](https://tex.z-dn.net/?f=y%3D4%2C%201)
2)
which can be rearranged as
.
![y=x^2+11x-12](https://tex.z-dn.net/?f=y%3Dx%5E2%2B11x-12)
Let's use elimination this time and subtract the first equation from the second:
![0=x^2-x-42](https://tex.z-dn.net/?f=0%3Dx%5E2-x-42)
Factor:
![(x-7)(x+6)=0](https://tex.z-dn.net/?f=%28x-7%29%28x%2B6%29%3D0)
![x=-6, 7](https://tex.z-dn.net/?f=x%3D-6%2C%207)
![y= -42, 114](https://tex.z-dn.net/?f=y%3D%20-42%2C%20114)
3)
![y=x^2-2x+6](https://tex.z-dn.net/?f=y%3Dx%5E2-2x%2B6)
![y=4x+10](https://tex.z-dn.net/?f=y%3D4x%2B10)
Let's set the two equations equal to each other through substitution:
![x^2-2x-6=4x+10](https://tex.z-dn.net/?f=x%5E2-2x-6%3D4x%2B10)
Move everything to one side:
![x^2-6x-16=0](https://tex.z-dn.net/?f=x%5E2-6x-16%3D0)
Factor:
![(x-8)(x+2)=0](https://tex.z-dn.net/?f=%28x-8%29%28x%2B2%29%3D0)
![x=-2, 8](https://tex.z-dn.net/?f=x%3D-2%2C%208)
![y= 2, 42](https://tex.z-dn.net/?f=y%3D%202%2C%2042)
Hope this helps!
Fu/ac=mu/bc so 27/36=mu/24 so mu= 18
Answer:
D, you simply just add 1.3 each time.
By taking square root of a number using calculator